Performance Measurement Analysis of Supply Chain Using The Supply Chain Operations Reference (SCOR) Method Version 12.0 (Studies on 25 kg Medium Rice Products at PT.XYZ) - Fauziah, Syifa Aulia; Muftiadi, Anang (Jurnal Ekonomi Pertanian dan Agribisnis, 2024)
This study aims to measure the performance of supply chain management in the 25 kg medium rice product at PT. XYZ. The object of this study is the supply chain performance of 25 kg medium rice as measured using the Supply Chain Operations Reference (SCOR) Version 12.0 method. The research method used is qualitative research with descriptive research type. The measurement results on level 1 metrics communicate Perfect Order Fulfillment performance (96% - Excellent), Order Fulfillment Cycle Time (100% - Excellent), Upside Supply Chain Adaptability (77% - Good), Cost of Goods Sold (89% - Marginal), and Cash-to-Cash Cycle Time (100% - Excellent). This study recommends PT. XYZ to improve its supply chain performance through Perfect Pick Put-Away, Inventory Based Accuracy, and Delay Inbound Supplier Shipment.